Whole genome shotgun sequence of Bacillus amyloliquefaciens TF28, a biocontrol entophytic bacterium. Issue 1 (December 2016) - Zhang, Shumei; Jiang, Wei; Li, Jing; Meng, Liqiang; Cao, Xu; Hu, Jihua; Liu, Yushuai; Chen, Jingyu; Sha, Changqing
Abstract Bacillus amyloliquefaciens TF28 is a biocontrol endophytic bacterium that is capable of inhibition of a broad range of plant pathogenic fungi. The strain has the potential to be developed into a biocontrol agent for use in agriculture. Here we report the whole-genome shotgun sequence of the strain. The genome size ofB. amyloliquefaciens TF28 is 3, 987, 635 bp which consists of 3754 protein-coding genes, 65 tandem repeat sequences, 47 minisatellite DNA, 2 microsatellite DNA, 63 tRNA, 7rRNA, 6 sRNA, 3 prophage and CRISPR domains.